Challenges and Strategies in Graduate Thesis Writing: Insights from a Literature Review - Sharma, Madhukar (Lumbini Journal of Language and Literature, 2024)
This paper aims to critically review the challenges faced by graduate students while writing thesis and strategies they employ to solve the problems of thesis writing. The research approach adopted in this study includes views, reviews, and critics put forward in different literature. Many students find it challenging to dedicate enough time for research, writing, and revisions, which often results in last minute efforts and heightened stress. Selecting an appropriate and manageable topic can be intimidating, as students may feel overwhelmed by the vast amount of available research. Additionally, many struggle with writing skills, making it difficult to express their ideas clearly and concisely, which can compromise coherence and academic quality. Inconsistent or insufficient feedback from advisors can also lead to confusion and frustration, affecting the overall quality of their thesis. This paper outlines the main challenges students encounter while writing their theses, including issues with time management, choosing a topic, writing abilities, and receiving feedback. It also discusses effective strategies for tackling these problems, such as developing organized timelines, obtaining support from peers or advisors, and enhancing writing skills through workshops and resources. Ultimately, the conclusion stresses the significance of addressing these challenges to improve the quality and success of thesis projects.